Effects of CETP inhibition on triglyceride-rich lipoprotein composition and apoB-48 metabolism - Diffenderfer, Margaret R; Brousseau, Margaret E; Millar, John S; Barrett, P Hugh R; Nartsupha, Chorthip; Schaefer, Peter M; Wolfe, Megan L; Dolnikowski, Gregory G; Rader, Daniel J; Schaefer, Ernst J (Journal of lipid research, 2012)
Cholesteryl ester transfer protein (CETP) facilitates the transfer of HDL cholesteryl ester to triglyceride-rich lipoproteins (TRL). This study aimed to determine the effects of CETP inhibition with torcetrapib on TRL composition and apoB-48 metabolism. Study subjects with low HDL cholesterol (<40 mg/dl), either untreated (n = 9) or receiving atorvastatin 20 mg daily (n = 9), received placebo for 4 weeks, followed by torcetrapib 120 mg once daily for the next 4 weeks. A subset of the subjects not treated with atorvastatin participated in a third phase (n = 6), in which they received torcetrapib 120 mg twice daily for an additional 4 weeks. At the end of each phase, all subjects received a primed-constant infusion of [5,5,5-(2)H(3)]L-leucine, while in the constantly fed state, to determine the kinetics of TRL apoB-48 and TRL composition. Relative to placebo, torcetrapib markedly reduced TRL CE levels in all groups (≥-69%; P < 0.005). ApoB-48 pool size (PS) and production rate (PR) decreased in the nonatorvastatin once daily (PS: -49%, P = 0.007; PR: -49%, P = 0.005) and twice daily (PS: -30%, P = 0.01; PR: -27%, P = 0.13) cohorts. In the atorvastatin cohort, apoB-48 PS and PR, which were already lowered by atorvastatin, did not change with torcetrapib. Our findings indicate that CETP inhibition reduced plasma apoB-48 concentrations by reducing apoB-48 production but did not have this effect in subjects already treated with atorvastatin.